SEE NO EVIL, HEAR NO EVIL: THE RISE AND FALL OF CHILD SEXUAL ABUSE IN THE 20th CENTURY - Collings, Steven J (PINS-Psychology in Society, 2025)
This paper examines the development of a medical perspective on child sexual abuse during the course of the 20th century and argues that such a perspective has not served the best interests of sexually abused children. An alternate social perspective is outlined, which would appear to have the potential to adequately address the needs of sexually abused children in the 21st century. The paper concludes by arguing that, despite its merits, the social perspective is likely to be of little value unless we can learn to more effectively see and hear the voices of child survivors.